Identification of sequence variants in key vitamin E genes from Elaeis guineensis Jacq. germplasm for development of DNA-based markers - Rufa'i, Babura Sulaiman (2018)
Vitamin E possesses important nutritional attributes that play various roles in human disease protection. The most well-known function of this noble compound is that of chain breaking antioxidant activity that scavenge free radical ions and reduce lipid peroxidation in membrane systems. Homogentisate geranylgeranyl transferase (HGGT) and homogentisate phytyl transferase (HPT) that catalyse the first committed step of tocotrienol and tocopherol biosynthesis, respectively are important in determining plant vitamin E composition. In Elaeis guineensis, there is high variability in the level of vitamin E among the germplasm materials from Angolan and Tanzanian origins. Therefore, the first objective of this study was to determine important sequence variants in these key vitamin E genes from E. guineensis germplasm materials that can be used for the development of DNA-based markers. The second objective was to analyse the effects of the sequence variants on vitamin E content and composition by overexpression of the HGGT gene and its mutant derivatives in Arabidopsis thaliana. Sequence analysis reveals no important variants in HPT gene that could be associated with low and high vitamin E content. However, the analysis reveals four SNPs at positions 193, 2225, 2429 and 6932 in the coding region of the HGGT gene that are associated with the vitamin E content. SNPs at 193 and 2429 positions lead to non-conservative amino acid changes in the sequence from Proline (CCT) in low vitamin E to Serine (TCT) in high vitamin E and from Methionine (ATG) in low to Isoleucine (ATA) in high vitamin E palms, respectively. SNP markers 193F/413R and 2225F/2429R were developed at these SNP locations for selection of high and low vitamin E germplasm materials in E. guineensis. Fourty one germplasm materials with different vitamin E level were screened to validate these two functional SNP markers using designed PCR-based mismatch primers. The results showed 100% success of the SNP-based markers in differentiating low and high vitamin E accessions. Furthermore, single nucleotide mutagenesis was successfully carried out to generate three cDNA sequence variants (193SNPHGGT, 2429SNPHGGT and HighSNPHGGT) with one or both SNP variants incorporated into the sequence of the commercial D×P genotype (LowSNPHGGT). The variant HGGT cDNA sequences together with the unmodified cDNA were successfully transformed into Arabidopsis thaliana. The relative expression levels of HGGT in T3 homozygous lines having the four different constructs separately showed significant (P≤0.005) up-regulated expression compared with untransformed wild type Arabidopsis. However, there was no significant difference observed in the expression among transgenic Arabidopsis plants harbouring the different HGGT constructs. This demonstrated that the different variants of the E. guineensis HGGT gene was expressed at about the same levels in the transgenic Arabidopsis. HPLC analysis indicates significant increase (p≤0.05) in the total tocotrienol content between wild type and all the four transgenic lines (1.50 – 1.82-fold increase). Similarly, significant difference (p≤0.05) in total tocotrienol was also recorded within the transgenic lines specifically between the two lines that harboured the two SNPs changes (HighSNPHGGT) and the one harboring the unmodified gene (LowSNPHGGT), which showed 1.22-fold increase. According to these results the two SNP variants introduced into the HGGT sequence of low vitamin E commercial variety affect the tocotrienol content and composition when analysed by functional characterization in Arabidopsis thaliana.